Evaluating the Antitumor Activity of Nintedanib by Solid Lipid Nanoparticle Drug Delivery System: In vitro and In vivo (Asian Journal of Pharmaceutics (AJP), 2026)
Introduction: Nintedanib was tested using the MTT assay on breast cancer cells and in vivo in mice bearingEhrlich ascites carcinoma (EAC). Nintedanib (NTD)-solid lipid nanoparticles (SLNs) showed better drugloading, release, and bioavailability, enhancing anticancer activity in vitro and in vivo. Materials andMethods: Cytotoxicity of NTD and NTD-SLNs were evaluated on Michigan Cancer Foundation (MCF)-7cancer cells using the MTT assay, determining cell viability. In vivo antitumor activity was assessed inEAC-bearing mice treated with NTD, NTD-SLNs, or standard 5-fluoro u , hematological parameters,and biochemical markers measured. Statistical analysis using one-way Analysis of Variance and Dunnett’stest showed treatment effects compared to the toxic control, with significance at P < 0.05. Results: NTDand NTD-SLNs showed dose-dependent cytotoxicity in MCF-7 cancer cells using the MTT assay, with thehighest inhibition at 200 μg/mL after 72 h. In vivo studies in EAC-bearing mice showed that NTD-SLNsimproved tumor suppression and restored hematological parameters toward normal, without toxicity. Overall,NTD-SLNs demonstrated stronger antitumor activity than pure NTD and effects comparable to the standarddrug 5-FU. Conclusion: In vitro studies showed that NTD-SLNs were more effective than free NTD due toimproved solubility and dissolution, leading to stronger antitumor activity. In vivo, both NTD and NTD-SLNsdemonstrated antitumor effects in EAC-bearing mice, though NTD-SLNs were not as effective as the standard5-FU. Overall, drug-loaded SLNs offer a promising approach for enhancing the bioavailability and antitumorpotential of poorly soluble drugs, such as NTD